Longitudinal Study on Low-Dose Aspirin versus Placebo Administration in Silent Brain Infarcts: The Silence Study. (3rd October 2018) - Maestrini, Ilaria; Altieri, Marta; Di Clemente, Laura; Vicenzini, Edoardo; Pantano, Patrizia; Raz, Eytan; Silvestrini, Mauro; Provinciali, Leandro; Paolino, Isabella; Marini, Carmine; Di Giuseppe, Matteo; Russo, Tommasina; et al.
Abstract : Background . We investigated low-dose aspirin (ASA) efficacy and safety in subjects with silent brain infarcts (SBIs) in preventing new cerebrovascular (CVD) events as well as cognitive impairment. Methods . We included subjects aged ≥45 years, with at least one SBI and no previous CVD. Subjects were followed up to 4 years assessing CVD and SBI incidence as primary endpoint and as secondary endpoints: (a) cardiovascular and adverse events and (b) cognitive impairment. Results . Thirty-six subjects received ASA while 47 were untreated. Primary endpoint occurred in 9 controls (19.1%) versus 2 (5.6%) in the ASA group (p=0.10). Secondary endpoints did not differ in the two groups. Only baseline leukoaraiosis predicts primary [OR 5.4 (95%CI 1.3-22.9, p=0.022)] and secondary endpoint-a [3.2 (95%CI 1.1-9.6, p=0.040)] occurrence. Conclusions . These data show an increase of new CVD events in the untreated group. Despite the study limitations, SBI seems to be a negative prognostic factor and ASA preventive treatment might improve SBI prognosis.EU Clinical trial is registered with EudraCT Number:2005-000996-16 ; Sponsor Protocol Number: 694/30.06.04.